Herpetofauna of the Western Region of Endau-Rompin, Johore, Peninsular Malaysia - B, Daicus; R, Hashim (Malaysian Journal of Science (MJS), 2004)
Thirty-three amphibian and 34 reptile species were recorded from the western region of Endau-Rompin. Of the amphibians, 32 were anurans and one caecilian; and of the reptiles 25 were lizards, 8 snakes and one turtle.